Genomic cloning and identification of a novel murine Cyp4a gene - Heng, Yee M. (1997)
The mouse cytochrome P450 4a family of genes is poorly characterised. This thesis describes a detailed study of these genes. Using primers derived from exon 1 of the mouse cyp3a10 cDNA sequence, a 1.4kb genomic fragment was cloned which contained the promoter region of the gene. Additionally, a lambda genomic library was screened with probes derived from the partial cDNA clones of the mouse cyp4a10 and cyp4a12. Originally, two classes of phage lambda clones were isolated. One clone, lambda 16, was partially sequenced and was found to contain the 3' end of the cyp4a12 gene. The second clone, lambda 4, was subcloned and found to be distinct from previously known murine cyp4a genes. This novel gene has been designated cyp4a14. To obtain the full cyp4a14 gene, the genomic library was rescreened. Lambda clone 12 was subsequently isolated from the library, which was found to contain exons 1 to 5 of Cyp4a14. In order to study the promoter region of cyp4a14, a pcr-based approach was undertaken to clone 4.4 kb upstream of exon 1 of the gene and a 1.2kb fragment has been sequenced. Cyp4a14 RNA was also found to be highly induced by a peroxisome proliferator, methylclofenapate. Primer extension analyses were performed to determine the start of transcription of Cyp4a14, which was mapped to a single T nucleotide 26bp upstream of the putative start site of protein translation. The promoter region of Cyp4a14 is highly similar to the corresponding regions of the rat CYP4A2 genes. however, similarity is dramatically reduced about 350bp upstream of the start of transcription, which coincides with the presence of two 358bp repeats in teh CYP4A2 gene. The promoter also contains a highly conserved 19bp element which is also found in the promoter regions of the CYP4A1 and CYP4A2 genes.